MESSAGE OF PEACE IN THE TEACHING OF ISLAM - Wawan Wahyuddin; Hanafi Hanafi (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2016)
This study aims to (1) describe the message of peace in the Qur'an, (2) describe the message of peace in the Hadith, and (3) describe the message of peace in the Medina Charter. The focus of this research is the message of peace in the teachings of Islam, which is broken down into three subfocus, namely (1) the message of peace in the Qur'an, (2) the message of peace in the Hadith, and (3) message of peace in Medina Charter. This study uses literature review. Data of this research is the theory and concepts of Islam, peace and war. The source of research data are books, papers, journals, and articles, as well as relevant research reports. It is concluded that (1) Messages of peace in the Qur’an is the outline (the main points), (2) Messages of peace in the Hadith is more detailed (description in detail), and (3) Messages peace in the Medina Charter is applicable (implementable). Al-Quran, the Hadith, and the Medina Charter, as well as historical facts have proved that Islam is a religion of peace (rahmatan lil Alamin) which is recognized not only by Muslims but also recognized by people of other faiths. Therefore, believers of other religions no longer need to worry about the development of Islam.